Constraints on the total coupling strengthto bosons in the iron based superconductors1. Issue 10 (26th September 2017) - Drechsler, Stefan‐Ludwig; Johnston, Steve; Grinenko, Vadim; Tomczak, Jan M.; Rosner, Helge
Abstract: Despite the fact that the Fe‐based superconductors (FeSCs) were discovered nearly 10 years ago, the community is still devoting a tremendous effort toward elucidating their relevant microscopic pairing mechanism(s) and interactions. At present, there is still no consistent interpretation of their normal state properties, where the strength of the electron–electron interaction and the role of correlation effects are under debate. Here, we examine several common materials and illustrate various problems and concepts that are generic for all FeSCs. Based on empirical observations and qualitative insight from density functional theory, we show that the superconducting and low‐energy thermodynamic properties of the FeSCs can be described semi‐quantitively within multiband Eliashberg theory. We account for the important high‐energy mass renormalizations phenomenologically, and in agreement with constraints provided by thermodynamic, optical, and angle‐resolved photoemission data. When seen in this way, many representative FeSCs with T c < 40 K studied so far are found to belong to an intermediate coupling regime (with the possible exception of some systems near a quantum critical point or in the vicinity of a Lifshitz transition). This finding is in contrast to the generally strong coupling scenarios proposed in the early period of the FeSC history. We also discuss several related issues, including the role of band shifts as measured by the positions of van Hove singularities, and the nature of a recently suggested quantum critical point in the strongly hole‐doped systems AFe2 As2 (A = K, Rb, Cs). Using high‐precision full relativistic GGA‐band structure calculations, we arrive at a somewhat milder mass renormalization in comparison with previous studies. From the calculated mass anisotropies of all Fermi surface sheets, only the ϵ ‐pocket near the corner of the BZ is compatible with the experimentally observed anisotropy of the upper critical field, pointing to its dominant role in the superconductivity of these three compounds. Abstract : Iron‐based superconductors (FeSCs) involve rich physics and tremendous effort is devoted towards elucidating their relevant microscopic pairing mechanism(s), i.e. the major bosonic mediated el–el interactions. Drechsler et al. examine several common FeSCs and illustrate problems and concepts that are generic for all FeSCs. Based on empirical data and qualitative insights from density functional theory, the authors show that the superconducting and low‐energy normal state thermodynamic properties of the FeSCs can be described semi‐quantitatively by multiband Eliashberg theory, often within an intermediately strong coupling regime. A doping–temperature phase diagram for FeSCs (red) and various competing magnetic phases (blue) is suggested.